Personality, Parenting and Deviance among Spanish Adolescents - Torrente, Ginesa; Vazsonyi, Alexander T. (Anales de Psicología / Annals of Psychology, 2012)
The goal of this work is to analyze the personality characteristics and interactions between parents and children that are related to diverse manifestations of deviant behavior in adolescence, such as alcohol and drug abuse, vandalism, and theft. We also analyzed parenting as a moderator in the relationship between personality and antisocial behavior. The sample is made up of 652 adolescents, 282 boys and 370 girls, mean 16.93 years (SD = 1). The results indicate that extraversion, agreeableness, and conscientiousness are associated with different measures of deviance. As expected, positive parenting processes (closeness, communication) are negatively associated with deviance, while conflict is positively associated. In addition, perceived conflict moderated the effects by Big Five personality constructs on measures of deviance.